Etika Bisnis Islam dalam Praktik Parkir Liar di Krisna Bali - Ai Netty Sumidartiny; Nopky Answara Putra Perdana (CV. Kalimasada Group, 2026)
Illegal parking fee collection remains a social and economic issue in various commercial areas, including locations that have implemented free parking policies. This phenomenon not only disrupts public order and visitor convenience but also raises ethical concerns in economic activities. This study aims to analyze the practice of parking fee collection at the Krisna shopping area in Denpasar, Bali, and examine its conformity with the principles of Islamic business ethics. The study employed a qualitative field research approach. Data were collected through observation, in-depth interviews, and documentation involving parking attendants and visitors selected purposively. Data validity was ensured through source and method triangulation, while data were analyzed using data reduction, data display, and conclusion drawing. The findings reveal that parking fees continue to be collected despite the area being officially designated as a free parking zone. This practice is inconsistent with the principles of shiddiq, amanah, ‘adalah, and taradhin due to the absence of clear information, legal authority, parking tickets, official tariffs, and accountability mechanisms, resulting in visitors not being entirely free to give money voluntarily. The practice contains elements of gharar (uncertainty) and zulm (injustice), but no direct element of riba (usury). The study concludes that illegal parking fee collection in free parking areas constitutes an Islamic business ethics issue that requires stronger supervision by business managers and local governments.